The Effect of Using CIDR and Various Doses of PMSG as Well as Genistein on the Reproductive Characteristics of Palu Fat-tailed Sheep - Mangun, Mardiah; Suyadi, Suyadi; Ihsan, Muhammad Nur; Marjuki, Marjuki (Jurnal Ilmu Ternak Universitas Padjadjaran, 2022)
The objective of this study was to observe the reproductive characteristics of Palu fat-tailed sheep affected by animal parities given pregnant mare serum gonadotropin (PMSG) and genistein (GEN) as a synthetic phytoestrogen. This study employed 32 ewes arranged in a completely randomized experimental design. The first factor was parity (P2 and P3) and second factor was a hormonal treatment as follows; H0 (14 d-controlled internal drug release or CIDR implant as control), H1 (CIDR+PMSG at 15 IU/kg BW, im injection), H2 (CIDR+GEN 0.1 mg/kg BW, iv injection); H3 (CIDR+PMSG at 15 IU/kg BW and GEN at 0.1 mg/kg BW, iv injection). Results indicated that all animals exhibited estrous and the onset for H1 was significantly earlier than for H2 and H0. The duration of estrous for P3 was significantly longer than for P2, while that for H1 was significantly longer than for H2 and H0. Gestation rate was 93.75%, birth rate was 83.33% and length of gestation was 147.76±1.54 d. Birth weight for P3 was significantly higher than for P2. It is concluded that CIDR, PMSG, and genistein enhanced the estrous characteristics in Palu fat-tailed sheep but did not affect litter size and birth weight.